Integration of Biblical Authority in Curriculum Design and Pedagogical Practice: Toward a Transformational Model of Christian Education - Yohanes Nduru; Yustini Laia; Listari Halawa (Proceeding of The International Conference on Religious Education and Cross - Cultural Understanding, 2026)
This study examines the integration of biblical authority into curriculum design and pedagogical practices as a foundation for developing a transformational Christian education model in a global, digital context. The main issue raised is the dichotomy between normative theological approaches and contemporary pedagogical practices that are often secular, leading to a weak integration of faith and learning in Christian education. The purpose of this study is to formulate an integrative model that harmonizes biblical authority with modern pedagogical approaches in a contextual, relevant, and applicable manner. The research method uses a qualitative approach through systematic literature study and conceptual analysis of various recent journals and books in the fields of Christian education, curriculum, and transformational pedagogy. The results show that the integration of biblical authority can be constructed through three main dimensions: epistemological (the Bible as a source of truth), curricular (the integration of biblical narratives into the curriculum structure), and pedagogical (learning practices oriented towards character transformation and spirituality). The research synthesis produces the "Biblical Transformative Curriculum-Pedagogy Integration (BTCPI)" model that emphasizes the relationship between theological truth, character formation, and the practice of faith. In conclusion, the holistic integration of biblical authority and modern pedagogy contributes significantly to developing students who are not only academically competent but also possess contextual spiritual and moral maturity.